Design implications on capital and annual costs of smallholder irrigator projects - A F Hards; J A du Plessis (Journal of the South African Institution of Civil Engineers, 2013)
While agricultural producers on commercially operated irrigation schemes will aim to achieve the recommended high crop yields, those on a smallholder irrigation scheme usually produce moderate to low crop yields. The water demand by these two irrigator types also differs and is reflected in the variations in crop yields. Because smallholder irrigators produce lower crop yields and use less water, they should use a system suited to this lower water demand. Many irrigation schemes have the opportunity for participants to assess their farming objectives and models. The irrigators can then use the assessment results to determine their water demands, reduce their infrastructure capacity and reduce their capital, operation and maintenance costs. On many smallholder schemes, the system has been designed for commercial crop yields and water use. If smallholders never achieve commercial levels of production, they have overcapitalised and subjected themselves to additional operational strain. In this study, six irrigation schemes based in the Eastern Cape were evaluated according to three levels of irrigation supply: a commercial irrigator, a smallholder irrigator and the commercial under-utilised irrigator. The irrigation infrastructure for each of the six schemes was designed, and the associated costs determined, for each level of supply. The study investigates the impact of different designs on the amount of water and land used, and resultant costs of the infrastructure. The results show that a smallholder irrigator using a scheme sized for commercial operation can have significantly higher (between 5% and 29%) annual operation and maintenance costs. The study clearly shows that the farmer type should be considered when designing each irrigation scheme.